2016
DOI: 10.5430/wje.v6n6p51
|View full text |Cite
|
Sign up to set email alerts
|

Combined Teaching Method: An Experimental Study

Abstract: The search for the best approach to business education has led educators and researchers to seek many different teaching strategies, ranging from the traditional teaching methods to various experimental approaches such as active learning techniques. The aim of this experimental study was to compare the effects of the traditional and combined (traditional plus active learning) teaching methods in the process of knowledge formation among future primary school teachers. Participants were randomly selected from av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Accordingly, the use of suitable pedagogics approaches is important in order to ensure a success learning process. According to Kolesnikova (2016), a combination of different pedagogical approaches and learning approaches could be considered by instructors to improve the process of teaching and learning. This was consistent with Hussein (2015) who found that the use of different teaching and learning methods, in particular, in class gaming was contributed to students learning experience.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the use of suitable pedagogics approaches is important in order to ensure a success learning process. According to Kolesnikova (2016), a combination of different pedagogical approaches and learning approaches could be considered by instructors to improve the process of teaching and learning. This was consistent with Hussein (2015) who found that the use of different teaching and learning methods, in particular, in class gaming was contributed to students learning experience.…”
Section: Introductionmentioning
confidence: 99%
“…The term teaching method refers to the general principles, pedagogy and management strategies used for classroom instruction. Teaching methods in the process of knowledge formation, the traditional teaching method and active learning pedagogies approaches are two major types of teaching approaches (Kolesnikova, 2016).…”
Section: Teaching Methodsmentioning
confidence: 99%
“…In the context of this study, 'traditional teaching approaches' refer to the usual methods used by educators to teach science subjects. According to Kolesnikova (2016), the traditional teaching method, also known as the lecture method, is very common in education. Based on this lecture method, the educator can deliver the message through the 'chalk-and-talk' method.…”
Section: Traditional Teaching Approachesmentioning
confidence: 99%
“…Meanwhile, in the last years or even decades, there has been a shift from teacher-center education to a learner-centred education (Bergsmann, Schultes, Winter, Schober & Spiel, 2019;Bonk & Cunningham, 2012). Effective teaching methods help to activate students' curiosity about a class topic, engage students in learning, develop critical thinking skills, keep students on task, engender sustained and useful classroom interaction, and, in general, enable and enhance the learning of course content (Kolesnikova, 2016). Furthermore, the modern method is a learning process controlled by the students.…”
Section: Introductionmentioning
confidence: 99%